LITERATURE OF RUSSIAN ABROAD ABOUT MILITARY SPECIALISTS IN THE RED ARMY DURING THE CIVIL WAR - I. S. Baklanova (Научный вестник МГТУ ГА, 2016)
The article considers the points of view presented in the literature of Russians abroad, regarding the number of military specialists who served in the Red Army during the Civil War.